"Shanghai" in Irkutsk Downtown. Ecology of the Chinese Market - Dyatlov, Victor; Kuznetsov, Roman (project baikal, 2014)
On the turn of the 1980s, a Chinese market named ‘Shanghai’ spontaneously appeared in the center of Irkutsk. Initially it was just a venue where several hundreds of small sellers sold goods brought from China. A primitive infrastructure included sheds, stalls, stores, public catering enterprises and toilets. Except the Chinese, sellers of many other nationalities appeared on the market. Development of the market caused many problems: insanitary conditions, crime situation, corruption among government and security agencies.
Keywords: small sellers; Chinese market; Shanghai; Irkutsk downtown